New upper cretaceous (Campanian) flora from James Ross Island, Antarctica - Iglesias, Ari (Ameghiniana)
I present a diverse previously unrecorded assemblage of leaves, cuticle, seeds and fruits from early-mid Campanian marine sediments, representing the first well-preserved macrofloristic record found in the Santa Marta Formation (north of James Ross Island, Antarctica). This new flora is diverse and consistent with the presence of forests under temperate and frost free climate; taxa include: a cycad (Zamiaceae), conifers (Araucaria, Araucarites, Brachyphyllum, and Pagiophyllum), several ferns (including Pteridaceae and Schizaeaceae) and angiosperms (including ?Cunoniaceae and Lauraceae). This record helps further our understanding of the vegetation of continental areas in the Antarctic Peninsula during the Late Cretaceous. Presento una diversa asociación previamente no registrada de hojas, semillas y frutos, en sedimentos marinos del Campaniano temprano—medio, representando el primer registro macroflorístico bien preservado en la Formación Santa Marta (norte de la isla James Ross, Antártida). La flora es consistente con la presencia de bosques bajo clima templado libres de heladas, incluyendo: una cycadal (Zamiaceae), coníferas (Araucaria, Araucarites, Brachyphyllum y Pagiophyllum), varios helechos (incluyendo Pteridaceae y ?Schizaeaceae) y angiospermas (incluyendo ?Cunoniaceae y Lauraceae). Este registro incrementa el conocimiento de la vegetación en áreas continentales de la Península Antártica durante el Cretácico Tardío. Fil: Iglesias, Ari. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina